2012
DOI: 10.1155/2012/806306
|View full text |Cite
|
Sign up to set email alerts
|

ALS and Frontotemporal Dysfunction: A Review

Abstract: Though once believed to be a disease that was limited to the motor system, it is now apparent that amyotrophic lateral sclerosis (ALS) may be associated with cognitive changes in some patients. Changes are consistent with frontotemporal dysfunction, and may range from mild abnormalities only recognized with formal neuropsychological testing, to profound frontotemporal dementia (FTD). Executive function, behavior, and language are the most likely areas to be involved. Screening helpful in detecting abnormalitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 103 publications
2
43
0
4
Order By: Relevance
“…58 Problems with compliance with therapy and support could contribute to this difference. 52,59 Alternatively, the difference in prognosis might simply reflect the disease burden (Figure 4).…”
Section: Cognitive Impairmentmentioning
confidence: 99%
“…58 Problems with compliance with therapy and support could contribute to this difference. 52,59 Alternatively, the difference in prognosis might simply reflect the disease burden (Figure 4).…”
Section: Cognitive Impairmentmentioning
confidence: 99%
“…Sensory nerves and the autonomic nervous system are generally unaffected, meaning the majority of people with ALS maintain hearing, sight, touch, smell, and taste. Cognitive function is generally spared for most people, although some (approximately 5%) may develop frontotemporal dementia (Achi and Rudnicki, 2012). A higher proportion of people (30%-50%) also have more subtle cognitive changes, which may be unnoticed but are revealed by detailed neuropsychological testing.…”
Section: Tbi and Alsmentioning
confidence: 99%
“…68 Contradicting this classical view that memory is relatively spared in ALS and FTD patients, a growing number of studies have recently reported severe and genuine memory impairments in these disorders. 72,[94][95][96] Indeed, a good proportion of pathologically confirmed FTD patients show significant episodic memory problems, indicating that MTL areas, particularly hippocampal and parahippocampal regions, are clearly affected in the syndrome 43,45,46,97 and that executive dysfunctions caused by frontal atrophy are not the main contributor of memory impairment in FTD. 43 As for ALS, memory deficits have been controversial and most studies link memory impairment to executive dysfunction.…”
Section: Clinical/neuropsychological Findingsmentioning
confidence: 99%